Examining the Teacher Practice in Musical Education - Cárdenas Cárdenas, Julián Andrés; Fuentes Vargas, Liseth Dayana (Universidad Pedagógica y Tecnológica de Colombia, 2020)
The Pedagogical Content Knowledge (PCK) is a concept that explains how the teacher transforms his own knowledge on the subject into understandable material for students. To address it, Park and Oliver propose a model of six components that interact in a predefined context. Aim of this research was to make explicit the PCK of a guitar specialist teacher during a plucked string class in 2018, at private school in Tunja (Boyacá). For this, the hexagonal model proposed by Park and Oliver was used based on a case study where the planning and recording of a class is analyzed, as well as an interview with the teacher. The results show that the teacher’s PCK is based on the practical knowledge of the instrument and the students, the representations and beliefs about the class and, the constant evaluation. In this way, the subject proposes to develop the understanding of the explained concepts, through instrumental execution that, at the same time, serves as a strategy and way of evaluating students